Deep-sea Bacteroidetes from the Mariana Trench specialize in hemicellulose and pectin degradation typically associated with terrestrial systems - Xiao-Yu Zhu; Yang Li; Chun-Xu Xue; Ian D. E. A. Lidbury; Jonathan D. Todd; David J. Lea-Smith; Jiwei Tian; Xiao-Hua Zhang; Jiwen Liu (Microbiome, 2023)
Abstract Background Hadal trenches (>6000 m) are the deepest oceanic regions on Earth and depocenters for organic materials. However, how these enigmatic microbial ecosystems are fueled is largely unknown, particularly the proportional importance of complex polysaccharides introduced through deposition from the photic surface waters above. In surface waters, Bacteroidetes are keystone taxa for the cycling of various algal-derived polysaccharides and the flux of carbon through the photic zone. However, their role in the hadal microbial loop is almost unknown. Results Here, culture-dependent and culture-independent methods were used to study the potential of Bacteroidetes to catabolize diverse polysaccharides in Mariana Trench waters. Compared to surface waters, the bathypelagic (1000–4000 m) and hadal (6000–10,500 m) waters harbored distinct Bacteroidetes communities, with Mesoflavibacter being enriched at ≥ 4000 m and Bacteroides and Provotella being enriched at 10,400–10,500 m. Moreover, these deep-sea communities possessed distinct gene pools encoding for carbohydrate active enzymes (CAZymes), suggesting different polysaccharide sources are utilised in these two zones. Compared to surface counterparts, deep-sea Bacteroidetes showed significant enrichment of CAZyme genes frequently organized into polysaccharide utilization loci (PULs) targeting algal/plant cell wall polysaccharides (i.e., hemicellulose and pectin), that were previously considered an ecological trait associated with terrestrial Bacteroidetes only. Using a hadal Mesoflavibacter isolate (MTRN7), functional validation of this unique genetic potential was demonstrated. MTRN7 could utilize pectic arabinans, typically associated with land plants and phototrophic algae, as the carbon source under simulated deep-sea conditions. Interestingly, a PUL we demonstrate is likely horizontally acquired from coastal/land Bacteroidetes was activated during growth on arabinan and experimentally shown to encode enzymes that hydrolyze arabinan at depth. Conclusions Our study implies that hadal Bacteroidetes exploit polysaccharides poorly utilized by surface populations via an expanded CAZyme gene pool. We propose that sinking cell wall debris produced in the photic zone can serve as an important carbon source for hadal heterotrophs and play a role in shaping their communities and metabolism. Video Abstract